1994
DOI: 10.1177/101269029402900205
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Televised Sports to the Spread of Sports Activities

Abstract: The French public opinion takes for granted that televised sports have played a great part in the expansion of sport practice. This opinion is shared by sport economists, television top experts and leaders of sports organizations. The statistical data analysis of recent surveys proves that televised sports have only a small influence on the practice and development of sport in France.The question dealt with in this paper is &dquo;When the viewer watches sport on television does he feel the need to do sport him… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…A trickle-down effect is partly based on the assumption that media coverage frames the way information is processed with favourable portrayals creating supportive attitudes (Ritchie, Shipway & Chen, 2010) and it was widely believed that watching sport on television motivates viewers to take part in sports (Irlinger, 1994). For events to attract a large television audience, coverage needs to reflect viewer interests and values (Green, 2001) and the ability of the Olympic Games to symbolise issues and present a wide range of narratives (McDaniel & Chalip, 2002) means that they retain an enduring ability to pull fragmented audiences onto the television networks (Slack, 1999).…”
Section: Events and Sport Participationmentioning
confidence: 99%
“…A trickle-down effect is partly based on the assumption that media coverage frames the way information is processed with favourable portrayals creating supportive attitudes (Ritchie, Shipway & Chen, 2010) and it was widely believed that watching sport on television motivates viewers to take part in sports (Irlinger, 1994). For events to attract a large television audience, coverage needs to reflect viewer interests and values (Green, 2001) and the ability of the Olympic Games to symbolise issues and present a wide range of narratives (McDaniel & Chalip, 2002) means that they retain an enduring ability to pull fragmented audiences onto the television networks (Slack, 1999).…”
Section: Events and Sport Participationmentioning
confidence: 99%
“…On retrouve ici un constat déjà fait dans un travail antérieur portant sur les rapports entre la pratique sportive et la consommation de sport télévisé (Irlinger, 1994): les différentes pratiques d'exercice, de communication et de consommation relevant du champ sportif tendent à s'associer, à se cumuler plutôt qu'à se concurrencer, ne serait-ce que sur le plan du temps investi.…”
Section: La Multipratique Des Compétiteursunclassified
“…They suggested that both activities, being involved and watching, play a significant and constantly changing role in shaping the participants' experience. These findings seem to challenge the literature in the realm of sports that suggested there is a weak relationship between participating in an activity and an earlier or subsequent choice to view (Burnett, Menon & Smart, 1993;Irlinger, 1994). Yet different from Lamont and McKay (2012), this work (Burnett, Menon & Smart, 1993;Irlinger, 1994) has not looked at immediate experiences on site, but into how viewing sport activities on television might spread participation.…”
Section: The Active-passive Divide Community and The World Gymnaestradamentioning
confidence: 64%
“…These findings seem to challenge the literature in the realm of sports that suggested there is a weak relationship between participating in an activity and an earlier or subsequent choice to view (Burnett, Menon & Smart, 1993;Irlinger, 1994). Yet different from Lamont and McKay (2012), this work (Burnett, Menon & Smart, 1993;Irlinger, 1994) has not looked at immediate experiences on site, but into how viewing sport activities on television might spread participation. More research is needed in other sports tourism settings to fully understand this phenomenon of merging and oscillating experiences of being actively involved and viewing.…”
Section: The Active-passive Divide Community and The World Gymnaestradamentioning
confidence: 64%